Babysafe reminder: preventing forgotten babies using IOT / Naufal Ismat Mohammad Hussin - Mohammad Hussin, Naufal Ismat (2024)
The "BabySafe Reminder" project takes advantage of the Internet of Things to tackle the pressing issue of protecting children from being left alone in vehicles. This all- inclusive solution incorporates temperature and weight sensors, an Arduino microcontroller, and a GSM module. The system is notable for including a DS18B20 temperature sensor to track the interior temperature of the car and a HX711 load cell to measure weight and confirm the presence of a child. One significant contribution to the project's sustainability is the use of a solar cell as an environmentally friendly power source. If the temperature increases above a certain threshold while the child is presented, the technology reminds parents through mobile phone. The GSM module notifies caretakers of the emergency by phoning them simultaneously. The "BabySafe Reminder" program strives to lower the risks involved in leaving young children alone by providing a reasonably priced, dependable, and easily navigable solution. The project's adoption potential is increased by enhancing safety and aligning with environmental consciousness through the integration of IoT technologies and a solar cell for sustainable power.